2013
DOI: 10.1021/cr400017y
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-Associated Genome Instability

Abstract: in Eukaryotes 8647 7. TAR Stimulation by Defective mRNP Biogenesis and Export 8649 8. R-Loops as Intermediates in TAR 8650 9. TAR and R-Loops during Class Switch Recombination (CSR) 8652 10. Instability of the rDNA Repeats 8653 10.1. TAR at the rDNA Region 8653 10.2. Fob1 and the Replication Fork Barrier (RFB) 8654 10.3. Chromatin Silencing to Prevent TAR at the rDNA 8654 11. Concluding Remarks and Perspectives 8654 Author Information 8655 Corresponding Author 8655 Notes 8655 Biographies 8655 Acknowledgments 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 338 publications
2
52
0
Order By: Relevance
“…It is known from many reports from bacteria to human cells that transcription stimulates recombination (Gaillard et al 2013). Consistent with recombination being the main pathway of repair of DSBs generated during replication, it is believed that most TAR events arise during replication as a result of transcription-replication collisions that cause the stalling and collapse of forks (Azvolinsky et al 2009;Bermejo et al 2009).…”
Section: Discussionmentioning
confidence: 94%
“…It is known from many reports from bacteria to human cells that transcription stimulates recombination (Gaillard et al 2013). Consistent with recombination being the main pathway of repair of DSBs generated during replication, it is believed that most TAR events arise during replication as a result of transcription-replication collisions that cause the stalling and collapse of forks (Azvolinsky et al 2009;Bermejo et al 2009).…”
Section: Discussionmentioning
confidence: 94%
“…There are many proposed models that could explain the sources of transcription-dependent mutagenesis. Some of these models include the following: recombination, DNA supercoiling, R-loops (RNA:DNA hybrids), non-B DNA, DNA damage, and rNTP incorporation (6,66,(75)(76)(77)(78)(79)(80)(81)(82)(83). These mechanisms are not mutually exclusive and may be contributing to transcription-dependent mutations collectively, and under different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work on phage transduction (Dul and Drexler 1988), illegitimate recombination in bacterial plasmids (Vilette et al 1992), RNAPII-mediated recombination between DNA repeats in S. cerevisiae (Thomas and Rothstein 1989), at the ADE6 locus of Schizosaccharomyces pombe (Grimm et al 1991) and in rodent cells (Nickoloff and Reynolds 1990) showed that TAR is a conserved feature. A survey of these and later examples of TAR from bacteria to mammals can be found in a recent review (Gaillard et al 2013).…”
Section: Transcription Stimulates Recombination From Bacteria To Humamentioning
confidence: 99%
“…Subsequent work on phage transduction (Dul and Drexler 1988), illegitimate recombination in bacterial plasmids (Vilette et al 1992), RNAPII-mediated recombination between DNA repeats in S. cerevisiae (Thomas and Rothstein 1989), at the ADE6 locus of Schizosaccharomyces pombe (Grimm et al 1991) and in rodent cells (Nickoloff and Reynolds 1990) showed that TAR is a conserved feature. A survey of these and later examples of TAR from bacteria to mammals can be found in a recent review (Gaillard et al 2013).Although the possibility that the impact of transcription on features such as chromatin structure or the channeling of DNA breaks into different types of repair has been considered an explanation of TAR, our current understanding favors TAR being the consequence of an increase in recombinogenic DNA damage caused by transcription. In yeast, DSBs generated by the homothallic switching (HO) endonuclease inducerecombinationtosimilar levelsregardlessof transcription being active or not (Weng et al 2000;Gonzalez-Barrera et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation